The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1093/mnras/staa556
|View full text |Cite
|
Sign up to set email alerts
|

Properties of giant molecular clouds in the strongly barred galaxy NGC 1300

Abstract: Star formation activity depends on galactic-scale environments. To understand the variations in star formation activity, comparing the properties of giant molecular clouds (GMCs) among environments with different star formation efficiency (SFE) is necessary. We thus focus on a strongly barred galaxy to investigate the impact of the galactic environment on the GMCs properties, because the SFE is clearly lower in bar regions than in arm regions. In this paper, we present the 12 CO(1 − 0) observations toward the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 56 publications
1
40
0
Order By: Relevance
“…The Atacama Large Millimeter/submillimeter Array (ALMA) makes this possible by reducing the time required to survey the CO emission at cloud-scale resolution across the disc of single nearby galaxy to ∼1 h each (e.g. Whitmore et al 2014;Leroy et al 2015;Pan & Kuno 2017;Faesi, Lada & Forbrich 2018;Hirota et al 2018;Kruijssen et al 2019b;Maeda et al 2020). ALMA also makes it possible to extend these studies beyond star-forming, disc galaxies to early-type galaxies (Utomo et al 2015;Davis et al 2017, Williams et al, in preparation;Chevance et al, in preparation) and ultraluminous infrared galaxies (Imanishi, Nakanishi & Izumi 2019, Saito et al, in preparation).…”
Section: Introductionmentioning
confidence: 99%
“…The Atacama Large Millimeter/submillimeter Array (ALMA) makes this possible by reducing the time required to survey the CO emission at cloud-scale resolution across the disc of single nearby galaxy to ∼1 h each (e.g. Whitmore et al 2014;Leroy et al 2015;Pan & Kuno 2017;Faesi, Lada & Forbrich 2018;Hirota et al 2018;Kruijssen et al 2019b;Maeda et al 2020). ALMA also makes it possible to extend these studies beyond star-forming, disc galaxies to early-type galaxies (Utomo et al 2015;Davis et al 2017, Williams et al, in preparation;Chevance et al, in preparation) and ultraluminous infrared galaxies (Imanishi, Nakanishi & Izumi 2019, Saito et al, in preparation).…”
Section: Introductionmentioning
confidence: 99%
“…NGC 604 and 30 Dor, one of the region Wong et al (2017) studied, are both sites of massive star formation surrounding giant H II regions and would both be places with high isocontour levels, so both of these locations could plausibly be affected by this truncation bias. It is worth noting that other extragalactic studies have found no strong correlation between size and linewidth (Colombo et al 2014;Maeda et al 2020).…”
Section: Size-line Width Relationmentioning
confidence: 75%
“…This leads to a direct correlation between M vir and the mass measured through other independent method (in our case the 13 CO luminosity). Recent extragalactic studies of NGC 300 by Faesi et al (2018) and NGC 1300 by Maeda et al (2020) have found a strong correlation between M vir and M lum and a low scatter in α vir near unity. We show in Fig.…”
Section: Molecular Mass-virial Mass Relationsmentioning
confidence: 93%
“…It has been reported that the properties of GMCs in the local group galaxies and nearby dwarf galaxies are similar to those of the Milky Way; e.g., M31 (Rosolowsky 2007), M33 (Rosolowsky et al 2003), IC10 (Ohta et al 1992;Leroy et al 2006). Further, extragalactic GMCs are detected on ∼ 50 pc scale by CO(1-0) observations with Plateau de Bure Interferometer and Atacama Large Millimeter/submillimeter Array (ALMA), and environmental dependence of those properties are investigated; e.g., M51 (Colombo et al 2014), M83 (Hirota et al 2018), NGC 1300 (Maeda et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…This is the first study of R 21 on ∼ 100 pc scale in a nearby barred galaxy. In NGC 1300, unlike the arm regions, star formation activity in the bar region is suppressed despite the presence of GMCs (Maeda et al 2020a). Since such significant differences in star formation activity are seen, NGC 1300 is thought to be an ideal laboratory to unveil the impact of the galactic environment on the R 21 .…”
Section: Introductionmentioning
confidence: 99%